Antioxidant activity test of propolis trigona sp extract from Cibubur using the dpph (1,1-diphenyl-2 picrylhydrazil) method - Sadiqy, M Chalid As (International Journal on ObGyn and Health Sciences, 2022)
Propolis is a resinous substance that comes from the wood and top of the plants gathered by bees, then mixed with wax and bee saliva. Propolis contains several active compounds such as flavonoids that could act as an antioxidant. The content of the active compound in propolis depends on the geographic factor, the bee species, and how to make the extract. The purpose of this research was to determine the antioxidant activity of propolis extracts Trigona sp from Cibubur with 96% ethanol using the DPPH (1,1-Diphenyl-2-Picrylhidrazyl) method. In this study the vitamin C was a positive control. The measurement of antioxidant activity used UV-Vis spectrophotometer with it's wavelength 517 nm. The results showed that the IC50 of propolis extract was 416.486 ppm while vitamin C was 5.96 ppm.